La «donna fiore» nel santuario di Hera alla foce del Sele. Un progetto per l'informatizzazione dei dati - Francesca Cantone (Les Carnets de l’ACoSt)
This project aims to illustrate the advantages of applying Information and Communication Technologies to the study of terracotta figurines from the Foce del Sele Sanctuary of Hera in south Italy